1983
DOI: 10.1128/aac.24.3.448
|View full text |Cite
|
Sign up to set email alerts
|

5-fluorocytosine susceptibility of pathogenic fungi in the presence of allopurinol: potential for improving the therapeutic index of 5-fluorocytosine

Abstract: The minimal inhibitory concentration of 5-fluorocytosine in 18 pathogenic fungal isolates was not altered by either allopurinol (100 microM) or oxypurinol (100 microM). Since allopurinol at this level clinically has been demonstrated to interfere with 5-fluorouracil anabolism, thereby reducing toxicity owing to 5-fluorouracil, allopurinol may be useful in counteracting the 5-fluorouracil-induced myelotoxicity observed in patients being treated with 5-fluorocytosine without interfering with the antifungal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This latter finding may be an important factor in determining whether the activity of 5-FC is fun gistatic (A. fumigatus and Cryptococcus neoformans) or fungicidal (Candida sp.) [80,81], In this respect, exo genously supplied purines, pyrimidines and some of their nucleoside analogues are known for their ability to antag onize the fungistatic activity of 5-FC [82,83], At doses of 100 itM, neither allopurinol nor oxypurinol altered the MIC values of 5-FC against 18 pathogenic fungal isolates [83]. Watanabe et al [84] reported the successful treat ment of 1 patient with pulmonary aspergillosis by intracav itary infusion of 5-FC.…”
Section: Miscellaneous Antifungal Compoundsmentioning
confidence: 99%
“…This latter finding may be an important factor in determining whether the activity of 5-FC is fun gistatic (A. fumigatus and Cryptococcus neoformans) or fungicidal (Candida sp.) [80,81], In this respect, exo genously supplied purines, pyrimidines and some of their nucleoside analogues are known for their ability to antag onize the fungistatic activity of 5-FC [82,83], At doses of 100 itM, neither allopurinol nor oxypurinol altered the MIC values of 5-FC against 18 pathogenic fungal isolates [83]. Watanabe et al [84] reported the successful treat ment of 1 patient with pulmonary aspergillosis by intracav itary infusion of 5-FC.…”
Section: Miscellaneous Antifungal Compoundsmentioning
confidence: 99%